Climate Change, Economy, and Food Security Nexus: An ARDL Analysis of Pakistan's Agriculture - Naveed, Tanveer Ahmad; Hanzla, Muhammad; Kanwal, Tayyaba; Parveen, Nazia (Pakistan Journal of Humanities and Social Sciences, 2025)
This study examines the short and long-term impacts of climate vulnerabilities, demographic shifts, and economic development on cereal yields and food security in Pakistan. Analyzing time series data for 1980-2022 this study establishes dynamic relationship, which is analyzed by employing Autoregressive Distributed Lag (ARDL) technique. Temperature increases exhibit an unambiguously negative effect on yields, while precipitation and sustainable land use have positive lagged effects. Population pressure demands immediate resource depletion but adds long term value through growth in agriculture. Its ability to affect food security is however hampered by structural factors even though there is economic development. The results highlight the need for proactive polices with regard to climate change and sustainable development that will help to reduce food insecurity in climate-sensitive countries.